PENGARUH PROMOSI DAN KINERJA PELAYANAN TERHADAP LOYALITAS NASABAH DENGAN KEPUASAN NASABAH SEBAGAI PEMODERASI: STUDI PADA BANK BUMN DI DIY - Ambar Kusuma Astuti; Agustini Dyah Respati (Fakultas Bisnis UKDW, 2015)
This study aimed to analyze the effect of promotions and service performance on customer loyalty andcustomer satisfaction as a moderating on state-owned bank in Yogyakarta. The sampling method usedin this study was twofold random sampling and quota sampling. Primary data were analyzed usingmultiple linear regression and moderated regression analysis. The findings in this study include theperformance of services has significant positive effect on customer loyalty, promotion has significantpositive effect on customer loyalty, the interaction effect of service performance on customer loyaltymoderated by customer satisfaction, and the interaction effect on customer loyalty promotionmoderated by customer satisfaction.Keywords: Promotion, Service Performance, Satisfaction, Loyalty